Analisis Postur Tubuh Pekerja Mebel Kayu Menggunakan Metode REBA: Studi Ergonomika Mengurangi Musculoskeletal Disorder - Salsabila, Alya; Simanungkalit, Marifa; Adhayuga, Farhan Agung; Anggraini, Bella Dewi; Pangihutan, Ruben; Mufidah, Zunanik; Fil’aini, Raizummi (Politeknik ATI Padang, 2025)
Wood furniture workers often face ergonomic challenges in their daily work activities, which involve manual tasks such as lifting, cutting, and assembling wooden components. These activities have the potential to cause musculoskeletal disorders (MSDs), which are disorders of the musculoskeletal system. MSDs can cause muscle pain, physical fatigue, and reduced work productivity in the long term if not properly addressed. This study aims to analyze the work posture risks of furniture workers using the Rapid Entire Body Assessment (REBA) method, designed to evaluate overall body posture during work activities. Data collection was conducted through direct observation on-site and video recording during the work process. This visual data was then analyzed using CorelDraw software to measure the workers' body posture angles, which were subsequently used to determine the REBA score for each work activity. The analysis results showed that out of the five main stages in the furniture production process, four of them had moderate to high ergonomic risk levels. The most risky stages are during wood cutting and assembly, where workers tend to bend or lift loads in an unideal position. Based on these results, the study recommends several improvement measures, including the use of lifting aids, adjusting the height of workbenches to match workers' body postures, and scheduling regular rest breaks. These steps are expected to reduce the risk of injuries caused by non-ergonomic work postures and improve the comfort and efficiency of furniture workers.